Classification and application of problem solving quality tools: A manufacturing case study - Hagemeyer, Catherine; Gershenson, John K.; Johnson, Dana M. (TQM magazine, 2006)
The complexity of problem solving requires use of quality tools to assist in the organization and analysis of information and data surrounding the concern. A proposed classification scheme for problem-solving tools allows the user to identify the correct tool at the proper time in the problem-solving process. This may assist the problem solver to efficiently and effectively work toward problem solution. The classification scheme, in the form of a matrix, identifies, organizes, and defines tools of the six sigma problem-solving process as taught and implemented at a large manufacturing company. The methodology was applied to a case study in a large manufacturing company related to an Air Conditioning (A/C) No Fill concern. However, since the matrix was not fully completed at the start of either the training or the project, the team was unable to begin using the developed matrix until midway through both. This posed some limitations in judging the efficiency and effectiveness of the matrix. Although this approach uses existing quality management and problem-solving tools, its novel application in the development of a more thorough approach to problem solving, aided by the classification of problem-solving tools may enable companies to more successfully and expeditiously reach proposed solutions.